Communicative Dissonance Management Among Religious Young Adults in Nightlife Contexts - Irmawati Oktavianingtyas; Nydia Fairley (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2026)
This study examined how religious young adults experience value-behavior inconsistency when engaging in nightlife drinking and clubbing, and how they communicatively managed the resulting tension. Cognitive dissonance theory and accounts theory served as complementary analytic frameworks, positioning dissonance reduction as both a psychological and an inherently communicative process. A qualitative design was employed, with semi-structured interviews conducted with eight college students aged 18 to 19 years at an Indonesian university, comprising four male and four female participants from Muslim and Christian backgrounds. Data were analyzed using reflexive thematic analysis. The findings revealed that participants consistently positioned religion as a foundational moral framework within which nightlife participation was interpreted as inconsistent with religious expectations. Dissonance was experienced primarily as post-behavioral emotional and identity-based discomfort, intensifying after leaving nightlife settings rather than during participation. Participants employed two broad communicative account-making patterns to manage dissonance, namely justification accounts involving boundary-setting and moral reframing, and apology and conciliation accounts involving repentance, prayer, and compensatory religious practices oriented toward the divine and the reflexive moral self. Dissonance reduction operated as ongoing communicative regulation rather than a single resolution.